MODELAGEM DE ESTUDOS EPIDEMIOLÓGICOS - Battisti, Iara D. E.; Battisti, Gerson; Reckziegel, Ciro; Jung, Inês; Dallepiane, Loiva; Franz, Ligia; Stumm, Eniva M.; Kirchner, Rosane; Leite, Marinês T. (Salão do Conhecimento, 2013)
Resumo